Mosaicism in von Hippel–Lindau disease with severe renal manifestations. (5th February 2013) - Wu, P; Zhang, N; Wang, X; Li, T; Ning, X; Bu, D; Gong, K
Abstract : von Hippel–Lindau (VHL) disease is an inheritable multisystem tumor syndrome characterized by multiple benign and malignant tumors affecting multiple organs. VHL is the result of a germline mutation in the VHL tumor suppressor gene. Molecular genomic analysis routinely confirms the clinical diagnosis. However, the use of molecular diagnostic methods can often be insufficient for the detection of mosaic germline VHL mutations, making the diagnosis of some cases of VHL difficult. Here, we report the case of a VHL mosaic patient with bilateral renal lesions in the absence of other VHL‐associated lesions. A VHL mutation was not originally detected by routine molecular testing. Nonetheless, the detection of a heterozygous c.194C>G (p.Ser65Trp) VHL mutation in the patient's daughter prompted further genetic assessment and eventually resulted in the finding of a mosaic c.194C>G (p.Ser65Trp) VHL mutation in the patient. The mutation rate was 18.8 ± 3.84% in peripheral leukocytes. As the frequency of VHL mosaicism remains underdetermined, the possibility of a diagnosis of mosaic VHL should be considered in patients with both typical and atypical VHL‐associated manifestations.